Fouling organisms on Perna perna mussels: is it worth removing them? (Brazilian Journal of Oceanography, 2007)
Perna perna mussel spat were suspended from ropes on a long-line cultivation, at Coqueiro´s Beach, Anchieta, South-eastern Brazil, in order to quantify the fouling community structure and its effects on growth and biomass of mussels. Half of the ropes had the fouling removed monthly, half had the foulingleft until the end of the experiment. Monthly samples of thirty mussels from each group were measured and their biomass determined. The fouling organisms were identified, quantified and their biomass evaluated on a monthly basis. After ten months, mussels on the cleaned treatment were significantly larger and heavier (ANOVA; P < 0.05; Bonferroni: unfouled >; fouled), showing that fouling reduced mussel development. The most abundant epibiont organisms in terms of biomass were the algae Polysiphonia subtilissima (29%) and Ulva rigida (10.3%), followed by the bryozoans Bugula neritina (13.6%) and Perna perna spat (10.6%). Over 97 taxa and 42,646 individuals were identified, crustaceans being the most abundant group, predominantly one amphipod Cheiriphotis megacheles (12,980 ind.). Species abundance was positively correlated with algal biomass, revealing the influence of algae on vagile fauna, which provide both food and shelter. The benefits of fouling removal are discussed because the majority of species are important feeding items to fishes and yet, the costs of its fouling control added to the associated mussel spat loss make this fouling removal of questionable value.